History of the Development of Sekolah Tinggi Teologi Satyabhakti: Sejarah Pengembangan Sekolah Tinggi Teologi Satyabhakti - Jefri Hinna (Sekolah Tinggi Teologi Satyabhakti, Malang)
Education is important for the current global changes. Education leads human beings to grow in knowledge as well. Charles A. Tidwel says, “Persons have an inherent capacity for growing and developing physically, intellectually, emotionally, and morally.” Furthermore, Tidwell emphasizes that human being is created by God as an intelligent being. Human beings are intelligent people and they will grow in their knowledge according to what they have learned in their life. They learn from what they have seen and heard, then will lead them into a change. To live means to change. Therefore, change is the essence of life. Change is inescapable and the Church today experience the change of the society.